Vav mediates Ras stimulation by direct activation of the GDP/GTP exchange factor Ras GRP1 - Caloca, María J. (Oxford University Press, 2003)
Here we describe a new signaling cross-talk between the Vav/Rac1 and Ras pathways that is established through the stimulation of RasGRP1, an exchange factor for Ras subfamily GTPases. This interaction is crucial for Ras activation in lymphoid cells, since this GTPase cannot become activated in the absence of Vav proteins. The activation of RasGRP1 requires both the generation of diacylglycerol via phospho lipase C-γ and the induction of actin polymerization, two responses induced by Vav and Rac1 that facilitate the translocation of RasGRP1 to juxtamembrane areas of the cell. Consistent with this, the cross-talk can be activated by tyrosine-phosphorylated wild-type Vav, oncogenic Vav and constitutively active Rac1. Conversely, Ras activation can be blocked in lymphocytes and ectopic systems using inhibitors affecting either phospholipase C-γ or F-actin polymerization. These results indicate that a relay mechanism exists in lymphoid and other cells helping in the generation of robust signaling responses by the Rac/Rho and Ras pathways upon receptor engagement.